Pengembangan Instrumen Penilaian Sikap Sosial Pembelajaran Tematik Kelas III SD - Bambang Tri Kuntoro; Naniek Sulistya Wardani (Peneliti.net, 2020)
The aims of this research and development are to produce social attitude assessment instrument products in thematic learning theme 7 subtheme 1 grade III SD; find out the visibility of social attitude assessment instruments in thematic learning theme 7 subthemes 1 grade III SD; understand the level of validity of social attitude assessment instruments in thematic learning theme 7 subtheme 1 grade III SD. The approach used is research and development (R&D) by adapting Sukmadinata's research procedures. The subjects in this study were grade III SD. The sampling technique is a random sampling quota technique, which is a technique that determines the number of samples that are owned and taken at random. The data collection technique used was nontest in the form of a questionnaire instrument using a Likert scale. The stages of the research consisted of three stages: a preliminary study; product developmen; and product testing. The results showed that the social attitude instrument out of 30 (thirty) statement items; the visibility of social attitude assessment instruments in thematic learning theme 7 subtheme 1, learning 6 grade III elementary school tested 3 times showed an average of α 0.920 then the instrument categorized as very reliable; the level validity of the social attitude assessment instruments tested at 20, 34 and 43 respondents showed a value of rhit 0.434; 0.418 and 0.414, so that the instrument was worth to used because it is quite valid.